Áreas protegidas diferem daquelas não protegidas quanto às fontes de energia e a posição trófica da ictiofauna de riachos? - Santos, Driele Delanira dos (2019)
The river continuum concept, developed for unperturbed aquatic systems, considers allochthonous inputs as main energy source for headwater streams' communities. To mitigate or prevent impacts, protected areas are created, preserving and protecting biodiversity of different ecosystems and its components. Since land use activities reduce native vegetation, just as riparian vegetation, these alterations effects in aquatic trophic chain can be investigated by the assimilation of this resources by the ichthyofauna through stable isotopes. Thus, it was tested the hypothesis that only in headwater streams from the protected area occurs greater allochthonous assimilation in the fishes’ biomass, which presents, even greater trophic level. The δ13C e δ15N values of producers and four fish species collected in three headwater streams from the protected area and three from the not protected area were used. The allochthonous material was the main carbon source for all species from both areas and they did not differ as for the trophic position. This study shows that primary producers in the not protected area are the first ones to reflect the anthropogenic activities' effects in its biomass, despite both areas resembling as for the impact presence. The greater assimilation of allochthonous sources by fish per se does not necessarily indicate a good conservation status, since the quality of these sources should also be evaluated. It is reinforced, therefore, that it is imperative to ensure effective protection of natural ecosystems, giving attention to all aspects of protected areas, from the creation or management and control.